Ethical aspects of normative theories of accounting - Rogowska, Beata (Annales. Etyka w Życiu Gospodarczym, 2019)
The aim of this article is to show ethical aspects of the so-called normative accounting theory (NT), with particular emphasis on the ethical and normative theory (ENT), important for the development of accounting as a science, taking into consideration its social function. Attention is focused on the so-called axiological layer with regard to the methodological foundation (pragmatic methods and related metascience) concerning the work of theorists in Western Europe. Although in the years 70s shall be considered as unscientific and begin the process of domination positive theory of accounting. It seems that the 21st century has brought about a rebirth of specific ethical and social topics in the field of accounting. The importance and usefulness of ethics in accounting have been growing due to changes in accounting and social needs driven by a turbulent environment, as well as changes in science.